The important role of furniture in our lives. - Dildora Urokova Ibragimovna, (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
Abstract Furniture is far more than a collection of functional objects; it serves as an essential bridge between human needs, cultural identity, psychological well-being, and environmental sustainability. This article examines the multifaceted role of furniture in daily life, from its historical evolution to its contemporary impact on health, productivity, social interactions, and interior spaces. Drawing on global design principles and Uzbek scholarly perspectives, it highlights how furniture shapes lifestyles, influences emotions, and addresses modern challenges such as urbanization and ergonomic demands. Through a comprehensive literature review and analytical discussion, the study underscores furniture’s transformative power in enhancing comfort, promoting health, and reflecting societal values. The findings emphasize the need for innovative, culturally sensitive, and sustainable design practices to meet future demands. This work contributes to a deeper understanding of furniture as a vital element of human existence, offering insights for designers, architects, and consumers alike.